Fetal genetic factors in pregnancy loss: Insights from a meta-analysis and effectiveness of whole exome sequencing. - Andrea Hadjipanteli; Athina Theodosiou; Ioannis Papaevripidou; Angelos Alexandrou; Nicole Salameh; Paola Evangelidou; Marios Tomazou; Andreas Mavrides; Sozos Fasouliotis; George Anastasiou; Andreas Stavroulis; Niki Agathokleous; et al. (PLoS ONE)
Spontaneous pregnancy loss commonly occurs during the first trimester and can be caused by various factors including chromosomal abnormalities and submicroscopic aberrations. After the first trimester, the etiology of most pregnancy losses remains undetermined. This study aims to fill this gap by an in-depth investigation of the fetal genome and its effect on pregnancy outcome. Data from 1016 spontaneously aborted fetuses previously referred for genetic testing (2017-2023) were used for meta-analysis. Fetuses were categorized based on gestational age and genetic test result. Additionally, 35 second-third trimester fetuses, that were spontaneously aborted, terminated or died neonatally, with abnormal ultrasounds and unrevealing routine genetic testing were collected. Trio-based whole-exome sequencing was performed for identification of fetal variants that may have caused the pregnancy loss. The meta-analysis revealed that 822 of 1016 fetuses (80.91%) were aborted during the first trimester, with 569 of 822 (69.22%) successfully diagnosed using conventional genetic testing. The remaining 194 fetuses (19.09%) were aborted during the second-third trimester. Of the 194 second-third trimester aborted fetuses, 163 (84.02%) lacked genetic diagnosis using conventional testing (karyotype and array-CGH). Aneuploidies were the leading cause of spontaneous pregnancy loss in both first and second-third trimester fetuses followed by polyploidies. Thus, the meta-analysis demonstrated that undiagnosed second-third trimester pregnancy losses are more likely to benefit from further genetic investigation. Application of whole exome sequencing on second-third trimester pregnancy losses, revealed causative variants in 6 of 33 families (18.18%), in genes linked to Mendelian disorders associated with the phenotypes of interest. Pathogenic findings were identified in two additional families in heterozygosity in genes following autosomal recessive inheritance. Accurate identification of variants in such genes creates new genotype-in utero phenotype associations, with the prospect of new additions in preconception/prenatal diagnostic panels. This study highlights the importance of whole exome sequencing in resolving undiagnosed pregnancy losses.